THE POTENTIAL OF ACTIVE COMPOUNDS Polyscias Scutellaria AS INHIBITORS IN CERVICAL CANCER WITH VIRTUAL SCREENING APPROACH - Muhammad Rizki Kurniawan; Aji Humaedi (Balai Besar Kimia dan Kemasan, 2021)
Cervical cancer is a gynecologic disease that has a high enough malignancy that affects women. In cervical cancer, it is known that the overexpression of Bcl-2 protein is 14.3% in non-invasive cervical carcinoma and 65.2% in invasive cervical carcinoma. The Bcl-2 protein is an important regulator of growth and differentiation pathways. Bcl-2 has anti-apoptotic activity but permeabilization occurs through the mitochondrial pathway, triggering the release of cytochrome c, which then interacts with Apaf-1 for caspase-9 activation and apoptosis occurs. This study aims to determine the mechanism of inhibition of overexpression of Bcl-2 protein by bioactive compounds from the Polyscias scutellaria plant with a virtual screening approach through in silico studies. The in silico study was carried out with the stages of tracking molecular targets, preparation, optimization, simulation and analysis of docking results. The results of the docking analysis showed that the bioactive compounds of the mangkokan plant provided inhibitory activity with gibbs energy values of -6.07, -5.18, -5.43 and -6.02, respectively. Thus the bioactive compounds from the mangkokan plant have potential as Bcl-2 inhibitors in cervical cancer.